Genealogi Fiqih Shafi'iyyah Dalam Tradisi Matan, Sharah dan Hasiyah - Chaidaroh, Umi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2009)
This study aims to trace the genealogy of Shafi'i fiqh through the tradition of writing matan, sharah, and hasyiah as a form of transmission and development of fiqh knowledge. The method used is qualitative with a historical-hermeneutic approach, through the study of classical literature and philological studies of the main works in the Shafi'i school. The results of the study show that the matan tradition plays a role as the core of the teachings, sharah as a conceptual explanation, and hasyiah as a critical note or commentary on the explanation. These three forms form a complex and dynamic scientific network, reflecting the dialectical process of thought and the continuity of scientific authority in the Shafi'i school. This research emphasizes that the tradition of fiqh literacy is an important methodological legacy in understanding the structure, flexibility, and continuity of the Shafi'i school of thought until the contemporary era.